Analisis Pola Sebaran Lahan Perkebunan Di Kecamatan Bungaraya Menggunakan Pendekatan Metode Average Nearest Neighbor (Studi Kasus: Kecamatan Bungaraya, Kabupaten Siak Sri Indrapura) - Hidayat, Ilham; Nasution, Salhazan; Candra, Feri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Bungaraya Subdistrict is one of the sub-districts in Siak Sri Indrapura Regency which continues to grow rapidly, starting with forest land and becoming productive plantation land as its population grows. In research conducted by the PPIG research team at the University of Riau, it has carried out mapping of Bungaraya District, the results of this study have provided the final result in the form of a visual form of the area. the distribution of land in Bungaraya Subdistrict, especially plantation land. Knowing the shape of the pattern of distribution of plantation land using the Average Nearest Neighbor method is a solution for monitoring land changes that occur. The purpose of this study was to observe and identify the distribution patterns of plantation land in Bungaraya District. This research uses qualitative methods with descriptive analysis. The identified plantation areas are then analyzed using the nearest neighbor analysis or Average Nearest Neighbor. The plantation land in Bungaraya Subdistrict is measured by a straight line distance between the centroid point of the plantation land and the centroid point of the nearest plantation land using the administrative map of the Bungaraya District land area through the Geographic Information System (GIS), namely ArcGIS. Analysis performed using manual calculations yielded 0.8 results, analysis using ArcGIS yielded 0.820553 results and analysis using pyhton programming yielded 0.7998641226905585 results, then the results of land distribution patterns in Bungaraya District were clustered (Clusstered). To see the accuracy of the results of the three analyzes, the test was carried out with the Confusion Matrix method from the test, which resulted in an accuracy of 98%. The clustering pattern becomes a reference material for the local government to make policies regarding land management that occurs.Keywords: Average Nearest Neighbor, Confusion Matrix, Plantation Land, Distribution Pattern